Opening Strategy: Evolution of a Precarious Profession - Whittington, Richard; Cailluet, Ludovic; Yakis-Douglas, Basak (British journal of management, 2011)
This paper takes the long view on the development of strategy as a profession, from the 1950s to today. We identify strategy as a structurally precarious profession, subject to cyclical demand and shifts in organizational power. This precariousness has increased with the secular shift towards more open forms of strategy‐making, with more transparency inside and outside organizations and more inclusion of different actors internally and externally. We analyse four forces – organizational, societal, cultural and technological – driving the evolution of strategy as a profession and discuss implications for the future of strategy work, for effective strategies, for strategy's professional bodies and for strategy research.